The effects of exposure to different clastogens on the pattern of chromosomal aberrations detected by FISH whole chromosome painting in occupationally exposed individuals - Beskid, Olena; Dušek, Zdik; Solanský, Ivo; Šrám, Radim J (Mutation research, 2006)
The pattern of chromosomal aberrations (CA) was studied by fluorescence in situ hybridization (FISH) technique (whole chromosomes #1 and #4 painting) in workers occupationally exposed to any of the four following conditions: acrylonitrile (ACN), ethyl benzene (EB), carcinogenic polycyclic aromatic hydrocarbons (c-PAHs), and irradiation in nuclear power plants (NPP), respectively. Decrease in the relative frequency of translocations was observed in EB group, and an increase in reciprocal translocations in ACN and NPP-exposed groups. An increase in a relative number of insertions was registered under all four conditions (significant at ACN, EB, c-PAHs, quasisignificant at NPP-exposed groups). Significant differences in the percentage of lymphocytes with aberrations on chromosome #1 (58.8+/-32.7%, versus 73.8+/-33.6% in the controls, P < 0.05), and chromosome #4 (47.0+/-34.1%, versus 29.4+/-32.2%, P < 0.01) were found in workers exposed to ACN. Similarly, a decrease in the proportion of cells with aberration on chromosome #1 (61.0+/-24.0%, versus 73.8+/-33.6%, P < 0.05) and an increase on chromosome #4 (45.6+/-24.6%, versus 29.4+/-32.2%, P < 0.05) were observed in workers exposed to EB. Frequency of aberrant cells (%AB.C.) as well as genomic frequency of translocations (F(G)/100) increased with age (P < 0.001). Aging also increased the percentage of translocations and reciprocal translocations (P < 0.05), but decreased the relative number of acentric fragments (P < 0.01). Smoking led to significantly increased F(G)/100 (P < 0.05), but did not affect the pattern of chromosomal aberrations. Our results seem to indicate that different carcinogens may induce a different pattern of chromosomal aberrations.
Keywords: financování organizované; dospělí; Regression Analysis; Smoking; akrylonitril; lymfocyty; Radiation, Ionizing; Adult; Acrylonitrile; kouření; malování chromozomů; lidé; Occupational Exposure; Chromosome Painting; mutageny; regresní analýza; kultivované buňky; ionizující záření; Financing, Organized; Cells, Cultured; Male; pracovní expozice; chromozomální aberace; polycyklické aromatické uhlovodíky; Polycyclic Aromatic Hydrocarbons; benzenové deriváty; Lymphocytes; Mutagens; Benzene Derivatives; mužské pohlaví; Chromosome Aberrations; Humans